Integration of IR4.0 with Geospacial SuperMap GIS and InfoWorks ICM - Kuok, King Kuok; Eva, Chen; Chiu, Po Chan (Solid State Technology, 2020)
Kota Samarahan, the capital of Samarahan division in Sarawak Malaysia, has experienced rapid development in the recent years. However, the intensive urban development has led to urban pluvial flood. Therefore, this research was carried out to reevaluate the sufficiency of existing drainage system at UniCentral, Kota Samarahan. Normally, water level simulation was carried out using InfoWorks Integrated Catchment Modelling (ICM) alone. However, the modelling process was found to be repetitive, time consuming, complicated and data may input incorrectly. Hence, it is proposed to integrate geospatial with IR4.0 at a global level, by incorporating SuperMap Geographical Information System (GIS) with InfoWorks Integrated Catchment Modelling (ICM) software for water level simulation. Physical data such as drain dimensions and flow were input into SuperMap GIS at initial stage. Thereafter, drainage information was imported into Infoworks ICM. InfoWorks ICM will simulate the water level in drainage system with rainfall intensity of 2, 5, 10, 20 and 50 years Average Recurrence Interval (ARI) and 30, 60, 120 and 360 minutes duration. The modelling process was found easier, simpler and efficient with this integration. Results revealed that Infoworks ICM is able to simulate the water level in the drainage system accurately. The water level in the drainage system was reduced significantly after a detention pond was added at downstream.